Resilience after adversity: an umbrella review of adversity protective factors and resilience-promoting interventions - Abate, Biruk Beletew; Sendekie, Ashenafi Kibret; Tadesse, Abay Woday; Engdaw, Tesfaye; Mengesha, Ayelign; Zemariam, Alemu Birara; Alamaw, Addis Wondmagegn; Abebe, Gebremeskel; Azmeraw, Molla (Frontiers in Psychiatry, 2024)
Resilience is the dynamic, adaptive process of maintaining or recovering mental health from stressors. Resilience after adversity can be fostered through protective factors and the implementation of interventions that promote resilience. Objective: To assess the effect of previous adversity, protecting factors, and resilience-promoting interventions to possess resilience after adversity in a global context. The study included English language articles searched using PubMed, Embase, Scopus, Web of Sciences, Cochrane Database of Systematic Reviews, Scopus, and Google Scholar published before 15 April 2024, which reported the effect of adversity, protecting factors, and/or resilience-promoting interventions to possess resilience after adversity were searched in a global context without limitation of age of population. The quality of the included studies was assessed using the Assessment of Multiple Systematic Reviews (AMSTAR). A weighted inverse variance random-effects model was applied to find the pooled estimates. The subgroup analysis, heterogeneity, publication bias, and sensitivity analysis were also assessed. Results: A total of 44 articles (n = 556920 participants) were included in this umbrella review. From the random-effects model analysis, the pooled effect of adversity on the development of resilience is found to be 0.25. The pooled effect of adversity-protective factors and resilience-promoting interventions after adversity were 0.31 and 0.42, respectively. The pooled effect of specific adversity protective factors was found to be 0.26, 0.09, 0.05, 0.34, 0.23, and 0.43 for the availability of support, cognitive ability, community cohesion, positive self-perception, religious involvement, and self-regulation, respectively. Whereas the pooled effect of specific resilience-promoting interventions was found to be 0.30, 0.21, 0.51, and 0.52 for cognitive behavior therapy (CBT) interventions, mindfulness-based interventions, mixed interventions, and resilience-promoting interventions, respectively. Conclusion: The findings of this umbrella review revealed that persons who experienced early adversity can develop resilience later in life. The study highlights the need to consider adversity protective factors such as availability of support (family, friends, and school), cognitive ability, community cohesion, positive self-perception, religious involvement, and self-regulation and resilience-promoting interventions including CBT interventions, mindfulness-based interventions, and mixed interventions to enhance resilience promotion programs.